Estimation of humidification load from humidifier column by convective heat transfer in water–air–vapour system - Iyuke, S.E.; Mohamad, A.B.; Daud, W.R.W. (Elsevier, 2001)
Due to the increasing awareness of the health benefits associated with the use of air humidification and its significance in other high-tech industries, an experimental and theoretical study was carried out to estimate humidification load in a convective heat transfer in water-air-vapour system. A simple gas bubbling method was employed for the experiments, while several models were developed to account for the applicability of the experimental data. The results showed agreement between the measured and the calculated data, and both purported that the humidification unit can be run successfully with airflow of 10-200 ml/min at the temperatures of 26-90°C. However, as from 300 to 1000 ml/min, the optimum operating temperatures decreased from 90°C to 35°C at 2 atm. At the operating conditions, the unit achieved relative humidity between 54% and 90% within the airflow of 10-1000 ml/min. The proposed unit characterisation method indicated a future advancement academically and industrially in this narrow but important subject matter.